Decision‐making and future planning for children with life‐limiting conditions: a qualitative systematic review and thematic synthesis. (12th April 2017) - Popejoy, E.; Pollock, K.; Almack, K.; Manning, J. C.; Johnston, B.
Abstract: Background: In the last decade, the number of children with life‐limiting and life‐threatening conditions in England has almost doubled, and it is estimated that worldwide, there are 1.2 million children with palliative care needs. Families and professionals caring for children with life‐limiting conditions are likely to face a number of difficult treatment decisions and develop plans for future care over the course of the child's life, but little is known about the process by which these decisions and plans are made. Methods: The purpose of this review is to synthesize findings from qualitative research that has investigated decision‐making and future planning for children with life‐limiting conditions. A systematic search of six online databases was conducted and identified 887 papers for review; five papers were selected for inclusion, using predefined criteria. Reference list searching and contacting authors identified a further four papers for inclusion. Results: Results sections of the papers were coded and synthesized into themes. Nineteen descriptive themes were identified, and these were further synthesized into four analytical themes. Analytical themes were 'decision factors', 'family factors', 'relational factors' and 'system factors'. Conclusions: Review findings indicate that decision‐making and future planning is difficult and needs to be individualized for each family. However, deficits in understanding the dynamic, relational and contextual aspects of decision‐making remain and require further research.